Effects of copper parenteral supplementation on the weight gain in fattening bulls - Juan García-Díaz (Revista MVZ Córdoba, 2017)
Objective. In order to evaluate the effect of copper parenteral supplementation on cupremia and weight gain in fattening bulls. Materials and methods. Fifty animals hybrids holstein and zebu were selected, with 18-20 months of age, 210 - 220 kg body weight, clinically healthy and in a system of intensive fattening. Two groups of 25 animals were divided, one control and another supplemented with 50 mg of intravenous Cu every 2 months to complete 3 applications; hemochemical indicators and weight gain were evaluated. The variables were compared using the t-Student test for independent samples and growth curves its parameters were determined. Results. Cu supplementation increased (p<0.001) the cupremia, hemoglobin and hematocrit, and (p<0.01) the average daily gain and the weight of the bulls, with increases in weight between .86 y 9.54 % for the treated group. Final Live weight (446 and 586 kg) and average daily gain (534 and 684 g/d) in control and treated group, respectively, were higher in the supplemented animals with Cu. Conclusions. The parenteral suplementation of 50 mg of Cu increased serum levels of Cu, hemoglobin, hematocrit and live weight gain in fattening bulls.